Study of the Vernier Effect Based on the Fabry–Perot Interferometer: Methodology and Application - Haitao Gao; Junxian Wang; Jian Shen; Shubing Zhang; Danping Xu; Yanan Zhang; Chaoyang Li (Photonics, 2021)
The optical Vernier effect is a powerful tool for improving the sensitivity of an optical sensor, which relies on the use of two sensor units with slightly detuned frequencies. However, an improper amount of detuning can easily cause the Vernier effect to be unusable. In this work, the effective generation range of the Vernier effect and the corresponding interferometer configuration are suggested and experimentally demonstrated through a tunable cascaded Fabry–Perot interferometer structure. We further demonstrate a practical method to increase the magnification factor of the Vernier effect based on the device bandwidth. Only the optical path length of an interferometer probe and the sensitivity of the measurement parameters are needed to design this practical interferometer based on the Vernier effect. Our results provide potential insights for the sensing applications of the Vernier effect.